UPAYA LEGALITAS UMKM MELALUI PEMBUATAN SURAT IZIN BERUSAHA (NIB) KURIPAN TIMUR LOMBOK BARAT - Satila , Susena; Anggraini , Mustika; Aditana, Santa; Jayawan, M. Indra; Magai , Milenus; Pratama, Dafa Rozzi; Widari, Algina; Aisyah , Nur; Salsabila , Elsa; Nurhayati, Nurhayati (Jurnal Wicara, 2023)
University of Mataram Thematic Real Work Lecture (KKN) with the theme "Preneur Village" which was held for 45 days in East Kuripan Village, Kuripan District, West Lombok which started from 19 December 2022 to 10 February 2023 with the aim of resolving MSME problems regarding the legality of Business Identification Numbers (NIB). Most of the MSMEs in East Kuripan Village do not have business licenses, while the MSMEs themselves have a very important role in maintaining economic stability in East Kuripan Village, apart from being agriculture and animal husbandry. Most of the people of East Kuripan Village work as traders by opening various types of businesses. The high participation of the community in the MSME field has caused the number of UMKM in East Kuripan Village to increase every year. However, MSME actors still lack knowledge regarding legality or business licenses, so that most MSMEs in East Kuripan Village do not yet have business licenses. To support the sustainability and development of MSMEs in East Kuripan Village, Mataram University Thematic KKN students try to help MSME actors to obtain legality which is marked by the Business Identification Number (NIB).